An Analysis of Teacher's Method in Teaching Reading Comprehension Through Online Learning - Lilis Sayuri Yuni; Ali Amran; Habib Syukri Nasution (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2022)
The study discusses about An Analysis of Teacher's Method in Teaching Reading Comprehension Through Online Learning. The objectives of this study were to: (1) to find out the teacher's methods in teaching reading comprehension through online learning at SMP Muhammadiyah 57 Medan, (2) to describe the teacher's methods in teaching reading comprehension through online learning at SMP Muhammadiyah 57 Medan. This study applied a descriptive qualitative method to analyze the data. The source of the data was obtained from English teacher in SMP Muhammadiyah 57 Medan. The data was taken 2 English teacher who teach in seventh, eighth, and nineth grade, to find what is method in teaching reading comprehension through online learning used. Data was accumulated by the use of questionnaire and interview, even as observation became used to verify how the teachers put into effect the methods in the course of their teaching and getting to know process via online studying. There were found out the methods used in teaching reading comprehension through online learning.